Phytochemical Constituents of Leaves Essential oils of Achillea fragrantissima (Asteraceae) from Iraq - Qader, Karzan O.; Al-Saadi, Sahar A.A. Malik; Faraj, Ibrahim M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
Essential oils of Achillea fragrantissima extract were prepared and analyzed by gas chromatography–mass spectrometry (GC-MS). A total of 57 phytochemical constituents of chemical compounds were identified in leaves of A. fragrantissima. The major constituents of the essential oil were camphor (34.50%), 1, 8-cineole (14.60%), artemisia ketone (10.25%), and 3-thujanone (7.82%). In addition, 43 components were present at <1%. From the 57 identified compounds, four of them was sesquiterpenes (7.01%), whereas 35 compounds were monoterpenes (61.40%).